Leveraging entrepreneurial knowledge competencies among academic librarians in Malaysia / Haziah Sa'ari, Rusnah Johare and Haslinda Mohamed - Sa'ari, Haziah; Johare, Rusnah; Mohamed, Haslinda (Faculty of Information Management, 2014)
Entrepreneurial knowledge competencies can be defined as a person's ability to recognize and exploit intellectual assets opportunities and transform them into innovations which will lead to innovation performance and competitive advantage. However, there has been little discussion on entrepreneurial knowledge competencies among academic librarians especially when the devastating effect of the global economic crisis on libraries has pressured them to use entrepreneurial approaches to generate income and explore innovative ways for sustainability. The main objective of this paper is to explore the entrepreneurial knowledge competencies among academic librarians and the outcomes measured by top management. This research capitalized on a qualitative technique which involved interpretative and descriptive analysis of words to gain in-depth understanding of a specific phenomenon. The study is significant to academic librarians and library management for improving competency and upgrading their innovation performance.